2005
DOI: 10.1039/b511184f
|View full text |Cite
|
Sign up to set email alerts
|

Delamination and restacking of a layered double hydroxide with nitrate as counter anion

Abstract: A layered double hydroxide (LDH) with nitrate as the counter anion (LDH-NO 3 with Mg/Al = 3) was, for the first time, successfully delaminated in formamide under ultrasonic treatment. Atomic force microscopy (AFM) images showed that a large part of the LDH was delaminated into single and double brucite layers (0.7-1.4 nm in thickness). The nano-sheets had disk-like shapes with a diameter of ca. 20-40 nm. Findings from AFM were in good agreement with the average hydrodynamic diameter determined using dynamic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
193
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(213 citation statements)
references
References 20 publications
17
193
0
3
Order By: Relevance
“…The intercalation of such ionic species into the inter-layers weakens the inter-layer binding and promotes exfoliation of the layered structures into individual 2D crystals. Liquid exfoliation using similar intercalation methods have been demonstrated in a broad family of layered functional materials such as transition metal oxides 20 and dichalcogenides 21 , layered double hydroxides 22 , h-BN 23 and even graphene 24,25 . Thus, it is suggested that liquid exfoliation via surface functionalization using oligomeric compounds is a general method, and the phenomenon observed here should be applicable to these other layered materials with the proper selection of compatible functionalizing species and solvent.…”
Section: Spray-coatable Oligomer-tethered Nanoplateletsmentioning
confidence: 99%
“…The intercalation of such ionic species into the inter-layers weakens the inter-layer binding and promotes exfoliation of the layered structures into individual 2D crystals. Liquid exfoliation using similar intercalation methods have been demonstrated in a broad family of layered functional materials such as transition metal oxides 20 and dichalcogenides 21 , layered double hydroxides 22 , h-BN 23 and even graphene 24,25 . Thus, it is suggested that liquid exfoliation via surface functionalization using oligomeric compounds is a general method, and the phenomenon observed here should be applicable to these other layered materials with the proper selection of compatible functionalizing species and solvent.…”
Section: Spray-coatable Oligomer-tethered Nanoplateletsmentioning
confidence: 99%
“…The absorption peak at 1,380 cm -1 was observed in LDH-NO 3 , which is attributable to the symmetric vibration of the interlayer nitrate anion (Figure 1Ba). [28][29][30][31]36] LDH-Fe(CN) 6 showed that an absorption peak at 1,380 cm [25,37,38] SEM images of the LDH-NO 3 and LDH-Fe(CN) 6 are shown in Figure 1C. As can be seen, the rosette aggregation for LDH-NO 3 was observed (Figure 1Ca).…”
Section: Physical Measurementsmentioning
confidence: 78%
“…In formamide some LDH dispersions were stable and transparent up to a concentration of 40 g l −1 , but formation of transparent gels was observed at concentrations higher than 5 g l −1 . 231 The delaminated LDHs could be restacked by adding sodium carbonate or ethanol. 231 Li et al 232 delaminated large crystals (10 µm) of Mg/Al LDH with a nitrate as the interlayer anion by simple shaking for 12 h in formamide.…”
Section: Delamination Of Ldhsmentioning
confidence: 99%
“…231 The delaminated LDHs could be restacked by adding sodium carbonate or ethanol. 231 Li et al 232 delaminated large crystals (10 µm) of Mg/Al LDH with a nitrate as the interlayer anion by simple shaking for 12 h in formamide. As one application example the obtained dispersion was subsequently used for a layer-by-layer selfassembly of the LDH nanosheets and anionic polymers to produce multilayer nanocomposite films.…”
Section: Delamination Of Ldhsmentioning
confidence: 99%